(untitled) (Biocenosis, 2025)
Currently, Tortuguero National Park safeguards biotic resources of particular importance for conservation efforts. Among these are the focal management elements (FMEs), which serve as an important tool for species preservation. However, it is necessary to update the data related to the species identified as FMEs and their status over time. This study provides a practical and descriptive overview of the specific characteristics of the FMEs in the area, using a qualitative approach based on the analysis of both primary and secondary information. As a result, 26 focal elements were identified; of these, 50% correspond to species classified as of “least concern,” while some have populations whose status remains unknown. Therefore, it is recommended to reevaluate the FMEs, prioritizing both umbrella species and those with limited distribution ranges or that are endemic to the country or region. Likewise, the FMEs should be updated based on a more thorough analysis of their baseline data; nevertheless, the current number of FMEs is considered appropriate. Finally, it is concluded that the study area has been a significant site for scientific research at least since the 1950s, although its designation as a national park occurred much later.